2018
DOI: 10.1097/sla.0000000000002977
|View full text |Cite
|
Sign up to set email alerts
|

Xenoantigen Deletion and Chemical Immunosuppression Can Prolong Renal Xenograft Survival

Abstract: Reducing xenoantigens in donor pigs and chemical immunosuppression can be used to achieve prolonged renal xenograft survival in a preclinical model, suggesting that if a negative cross-match can be obtained for humans then prolonged survival could be achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
144
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(157 citation statements)
references
References 43 publications
4
144
0
1
Order By: Relevance
“…With the increasingly encouraging results being achieved in pig‐to‐non‐human primate (NHP) organ transplantation models, particularly of kidney and heart xenotransplantation, initial limited clinical trials in carefully selected patients with end‐stage organ failure are drawing closer. With an increasing array of genetically engineered pigs becoming available, the question can be raised as to which combination of genetic modifications will be either optimal or necessary for an initial clinical trial.…”
Section: Introductionmentioning
confidence: 99%
“…With the increasingly encouraging results being achieved in pig‐to‐non‐human primate (NHP) organ transplantation models, particularly of kidney and heart xenotransplantation, initial limited clinical trials in carefully selected patients with end‐stage organ failure are drawing closer. With an increasing array of genetically engineered pigs becoming available, the question can be raised as to which combination of genetic modifications will be either optimal or necessary for an initial clinical trial.…”
Section: Introductionmentioning
confidence: 99%
“…Despite tremendous progress in the field , xenotransplantation won’t become clinical routine until the remaining issues have been thoroughly addressed. Currently, hyperacute rejection can be successfully prevented by transgenic expression of human complement regulators and knocking out the gene of the 1,3 galactosyltransferase.…”
Section: Discussionmentioning
confidence: 99%
“…In recent animal studies, long survival times have been reported for transgenic kidneys with GTKO and human complement regulator in absence of thrombomodulin. The results showed that TMA was still developing, indicating that this might be an unsolved issue in the long term . In these models, GTKO and a human complement regulator were combined with an immunosuppressive regime including a costimulation blockade.…”
Section: Discussionmentioning
confidence: 99%
“…Their encouraging data, obtained in a challenging experimental model, support the results achieved in life-supporting pig-to-nonhuman primate kidney transplantation models, where graft survival has extended to many months or even longer than one year. [2][3][4][5] The Munich group appears to have overcome-at least to a significant extent-two of the hurdles that limited success of pig OHT.We would like to make what we hope are constructive comments on these two topics.The first hurdle is achieving immediate and persistent graft function. The perfusate used to preserve the pig hearts contained thyroid hormone, and this may be a major factor in its success as there is a great deal of evidence going back many years that triiodothyronine (T3) maintains or replaces myocardial energy stores and improves cardiac function.…”
mentioning
confidence: 99%
“…Their encouraging data, obtained in a challenging experimental model, support the results achieved in life-supporting pig-to-nonhuman primate kidney transplantation models, where graft survival has extended to many months or even longer than one year. [2][3][4][5] The Munich group appears to have overcome-at least to a significant extent-two of the hurdles that limited success of pig OHT.…”
mentioning
confidence: 99%